2018
DOI: 10.14814/phy2.13552
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol supplementation alters intramuscular apoptotic signaling following acute resistance exercise

Abstract: The purpose of this study was to examine the effects of 28‐days of supplementation with an aqueous proprietary polyphenol blend (PPB) sourced from Camellia sinensis on intramuscular apoptotic signaling following an acute lower‐body resistance exercise protocol and subsequent recovery. Untrained males (n = 38, 21.8 ± 2.7 years, 173.4 ± 7.9 cm, 77.6 ± 14.6 kg) were randomized to PPB (n = 14), placebo (PL; n = 14) or control (CON; n = 10). Participants completed a lower‐body resistance exercise protocol comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…[65][66][67][68][69] The use of ultrasound during the pre-microbiopsy procedure was reported in 7 studies to safely identify and verify the muscle group depth, and subcutaneous adipose tissue thickness for both vastus lateralis and other muscle groups for sampling. 35,36,45,46,48,50,70 One study reported measuring skinfold thickness to estimate the depth of the biopsy needle 69 ; however, they did not report their protocol. Prior to the introduction of the microbiopsy needle, numerous authors reported that an incision was made in the skin and fascia with a hypodermic needle (14, 18, and 23 G) 23,50,71,72 or a co-axial/ cannula introducer 35,37,55,[73][74][75][76][77][78][79] to create or maintain a "pilot hole" for multiple passes if the study design required larger sample size (mg) per time point for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[65][66][67][68][69] The use of ultrasound during the pre-microbiopsy procedure was reported in 7 studies to safely identify and verify the muscle group depth, and subcutaneous adipose tissue thickness for both vastus lateralis and other muscle groups for sampling. 35,36,45,46,48,50,70 One study reported measuring skinfold thickness to estimate the depth of the biopsy needle 69 ; however, they did not report their protocol. Prior to the introduction of the microbiopsy needle, numerous authors reported that an incision was made in the skin and fascia with a hypodermic needle (14, 18, and 23 G) 23,50,71,72 or a co-axial/ cannula introducer 35,37,55,[73][74][75][76][77][78][79] to create or maintain a "pilot hole" for multiple passes if the study design required larger sample size (mg) per time point for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the use of a superficial lidocaine/prilocaine cream or lidocaine tape as a local anesthetic prior to the microbiopsy procedure 65–69 . The use of ultrasound during the pre‐microbiopsy procedure was reported in 7 studies to safely identify and verify the muscle group depth, and subcutaneous adipose tissue thickness for both vastus lateralis and other muscle groups for sampling 35,36,45,46,48,50,70 . One study reported measuring skinfold thickness to estimate the depth of the biopsy needle 69 ; however, they did not report their protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG was reported to reduce chondrocyte apoptosis during osteoarthritis in rat models by activating autophagy [ 105 ]. Green tea supplementation could effectively suppress the activation of autophagy inhibitors, thereby reducing muscle damage [ 106 ] and reducing ROS accumulation [ 107 ].…”
Section: Herbal Teas and Autophagymentioning
confidence: 99%
“…Finally, 2 studies unexpectedly showed increased CK levels in the groups that received GT and BT supplementation compared with the placebo group (24,61). The authors suggested that the use of muscle biopsies could have influenced muscle damage and inflammation results.…”
Section: Muscle Damagementioning
confidence: 99%